Improvement of mechanisms for ensuring sustainable enterprise development under contemporary challenges - Wang, Zhenyu (Харківський національний автомобільно-дорожній університет, 2025)
The qualification paper examines the essence of sustainable enterprise development and analyzes the mechanism for managing it under contemporary challenges. The main performance indicators and the internal environment of a road transport enterprise are analyzed, while the external operating environment is assessed to identify key development drivers and constraints. Based on the results of the assessment of functional, market, economic, and social potential, strategic actions are developed for each identified component of enterprise potential as a foundation for improving sustainability management mechanisms. Within the framework of the proposed strategic actions, practical recommendations are substantiated, including the implementation of a GPS vehicle monitoring system. The system enables real-time vehicle monitoring, improving efficiency, safety, and environmental performance, with its feasibility and economic efficiency justified. Forecast assumptions indicate that the implementation of the proposed strategic actions, particularly the introduction of GPS vehicle monitoring, will reduce operating costs, improve vehicle utilization and safety, enhance customer service, and decrease environmental impacts, thereby supporting sustainable enterprise development.
Keywords: sustainable development; management; management mechanism; potential; gps monitoring; assessment; efficiency